DOMESTICATION AND FOREIGNIZATION APPLIED TO TRANSLATION OF SELECTED QUOTATIONS BY A NOVICE TRANSLATOR - Alhadi, Fadhil Mochsin Faisal (2016)
This paper was aimed at finding out categories of culture-specific items in the translation of selected quotations on LINE online dictionary translated by a novice translator and figuring out which strategy between domestication and foreignization is more dominating in translating meaning of the culture-specific items. A descriptive qualitative research method was used in this research. From 2609 quotations, there were 228 culture-specific items found. Categories of CSIs proposed by some scholars, Newmark (1988), Ke Ping (1999) and Espindola & Vasconcellos (2006) were used then 15 categories were found, those were anthroponym (9.2%); ecology (4.8%); fictional character (2.6%); forms of entertainment (2.6%); ideational system (10.1%); linguistic system (0.4%); material culture (3.5%); means of transportation (1.8%); measuring system (4.4%), organization, customs, activities, procedure and concept (15.4%); scholastic reference (0.4%); social system (21.1%); techno-economic system (10.1%) and toponym (11.4%). 11 procedures of translation proposed by Newmark (1998), Harvey (2000) and Vina & Darbelnet (Cited in Munday, 2001) found among the categories of CSIs which 7 of them belong to domestication namely accepted standard translation (4.4%); cultural equivalent (5.3%); descriptive translation (3.1%); functional equivalent (0.4%); modulation (0.4%); naturalization (20.2%); transposition (1.8%); and 4 of them to foreignization which include calque (0.4%); gloss (2.6%), literal translation (43%) and transference or borrowing (18.4%). Strategy of foreignization was preferred in rendering cultural specific items with 64% and domestication strategy was composed of 36%. From the research, it was found that despite the dominance of foreignization strategy, the meaning of cultural specific items was not significantly meaningless but still meaningful.; Penelitian ini bertujuan untuk mengetahui kategori culture-specific items yang terdapat di terjemahan dari kutipan yang ada di kamus online LINE yang diterjemahkan oleh penerjemah pemula, selain itu, tujuan kedua adalah mengetahui strategi penerjemahan mana yang lebih dominan antara domestication dan foreignization dalam mengartikan arti dari culture-specific items. Desain deskriptif-kualitatif digunakan di penelitian ini. Dari 2609 kutipan, terdapat 228 culture-specific items yang ditemukan, terdiri dari anthroponym (9.2%); ecology (4.8%); fictional character (2.6%); forms of entertainment (2.6%); ideational system (10.1%); linguistic system (0.4%); material culture (3.5%); means of transportation (1.8%); measuring system (4.4%), organization, customs, activities, procedure and concept (15.4%); scholastic reference (0.4%); social system (21.1%); techno-economic system (10.1%) dan toponym (11.4%). 11 prosedur penerjemahan ditemukan dalam menerjemahkan culture-specific items, 7 di antaranya termasuk ke dalam domestication, yaitu accepted standard translation (4.4%); cultural equivalent (5.3%); descriptive translation (3.1%); functional equivalent (0.4%); modulation (0.4%); naturalization (20.2%); transposition (1.8%); dan 4 diantaranya termasuk ke dalam strategi foreignization yang terdiri dari calque (0.4%); gloss (2.6%), literal translation (43%) and transference or borrowing (18.4%). Strategi foreignization mendominasi dengan persentase 64% dan domestication dengan 36%..